Deep-red to near-infrared luminescence from Eu2+-trapped exciton states in YSiO2N. Issue 7 (2nd February 2022) - Kitagawa, Yuuki; Ueda, Jumpei; Xu, Jian; Nakanishi, Takayuki; Takeda, Takashi; Hirosaki, Naoto; Tanabe, Setsuhisa
Abstract : Eu 2+ -Trapped exciton states in YSiO2 N show anomalous deep-red to near-infrared luminescence under violet-blue light illumination. Abstract : The valence state of Eu ions doped in inorganic compounds is easily influenced by the synthesizing conditions. In this study, X-ray absorption spectroscopy revealed that almost half of Eu ions incorporated in the YSiO2 N host were reduced into the divalent state through the sintering process at 1600 °C under a N2 gas atmosphere without any annealing processes. The prepared Eu 2+/3+ -doped YSiO2 N sample showed anomalous deep-red to near-infrared luminescence below 300 K under violet light illumination, whose luminescent properties are discussed through detailed spectroscopic analyses. In the photoluminescence spectra at 4 K, the broad luminescence band ranging from 550 to 1100 nm with a large Stokes shift of 5677 cm −1 was observed, assigned to the recombination emission related to the Eu 2+ -trapped exciton state. The temperature dependence of luminescence lifetime suggests that the thermal quenching of Eu 2+ -trapped exciton luminescence takes place through complicated processes in addition to thermal ionization. The energy diagrams based on the spectroscopic results indicate that Eu 2+ -trapped exciton luminescence in the YSiO2 N:Eu 2+/3+ sample was observed because all the Eu 2+ : 5d excited levels are degenerated with the host conduction band, and the relatively stable Eu 2+ -trapped exciton state in the Y 3+ sites is formed just below the conduction band bottom. A comprehensive discussion on the deep-red to near-infrared luminescence in the YSiO2 N host could give new insights into the mechanism of Eu 2+ -trapped exciton luminescence in Y 3+ sites, which has potential in near-infrared emitting devices.